A critical re-assessment of the primary productivity of the Yellow Sea, East China Sea and Sea of Japan/East Sea Large Marine Ecosystems. (May 2019) - Yoo, Sinjae; Kong, Christina Eunjin; Son, Young Baek; Ishizaka, Joji
Abstract: Despite the importance of the primary production in coastal Large Marine Ecosystems, the complex bio-optical properties in some coastal waters make the estimation of primary productivity using satellite data quite challenging. Here we critically reviewed the accuracy of parametrization of three core variables, i.e. chlorophyll-a, chlorophyll-specific photosynthetic rate, and euphotic depth, in the Yellow Sea, East China Sea, and Sea of Japan/East Sea Large Marine Ecosystems. We also compared the annual primary productivity estimates of the three Large Marine Ecosystems by a depth-integrated model with those from two other global assessments, which used different primary productivity models: an absorption-based model, and a time and depth-resolved model. Our assessment suggests that 1) accurate parametrization of the core variables is more important than choosing a primary productivity model, and 2) the previous global Large Marine Ecosystem assessments might have overestimated the annual primary productivity in the Yellow Sea by a factor of 2 or so.